Gambaran Fertilitas Masyarakat Palu Yang Melakukan Pemeriksaan Analisa Kuantitatif Sperma di Laboratorium Kesehatan Palu - Musjaya M. Guli; Prita Permatasari (Biocelebes, 2012)
Research about decription of fertility of Palu sociaty who did analysis quantitative sperm examination at the Palu Healhty Laboratory was conducted from February – March 2011. The research aimed to know the description of Palu sociaty who did analysis quantitative sperm examination, describe the factor that be related to quality os sperm, and also to find abnormalities in sperm based on the description of fertility from quantitative analysis of sperm that mentioned. From 99 samples that eligible, factors related to sperm quality can be evaluated from macroscopic and microscopic examination. By macroscopic, the average value of cerment volume ranged from 1,6 to 5,0 ml, cement pH ranged from 7,6 to 8,0, cement liquefaction ranged from 36 to 60 minutes, and cement viscosity ranged from 0,6 to 5,0 cm. Microscopicallay, the avarage value the total number of sperm ranged from 61 to 108 million sperm/ ejakulate , sperm concentration ranged from 15,6 to 30 million /ml ejakulate , sperm motility ranged from 2-98%, sperm morphology ranged from 5 to 25%, and leucocyte sperm ranged from 0 to 2 million/ ml ejakulate. These factors are interrelateted to each other. From the description of the factors related to sperm quality was obtained subfertil conditions were 59 patients, there were 10 patients with fertile conditions, and more number of pariens with infertile conditions, there were 30 patients. This is supported by many abnormalities including Teratozoosoermia with total 33 patients, Oligoastenoteratozoospermia equal to 31 patients, Astenoteratozoospermis equal to 16 patients, Oligoteratozoospermia equal to 8 patients , and 1 patient each of Asten ozoospermia and Cryptozoospermia. Key words: Sperm, quantitative analysis of sperm, fertility.